RELEVANSI FINANCIAL SUSTAINABILITY MEASURES TERHADAP MANAJEMEN LABA: STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PRIMER DAN SEKUNDER YANG TERDAFTAR DI BEI PERIODE 2017-2019 - Vivian Witjaksono; Felizia Arni Rudiawarni (Akuntansi dan Teknologi Informasi, 2022)
Earnings management has become one of the most crucial issues in a company that can affect the condition of its financial statements. Financial reports are one of the maps that provide sources of information for internal and external parties. This study aims to determine the relevance of financial sustainability measures to the level of earnings management. The method used in this research is linear regression. The objects used in this study are those included in the primary and secondary sector categories listed on the Indonesia Stock Exchange in 2017-2019 with a total sample of 675 firms in 3 years. This study uses Modified Jones Model (Dechow et al., 1995) to detect earnings management behavior. The results of this study indicate that previously managed earnings and efficiency ratio have a significant negative effect on earnings management. In addition, liquidity positively affects earnings management. While leverage has no effect on the level of earnings management. It can be concluded that financial sustainability factors are relevant to earnings management behavior.